Contribution of School Well-being and Emotional Intelligence to Student Engagement in Learning - Roza Eva Susanti; Firman Firman; Daharnis Daharnis (International Journal of Applied Counseling and Social Sciences, 2020)
This study aims to analyze school well-being, emotional intelligence and student engagement in learning. The research was conducted using descriptive quantitative methods. The study population was 768 students of SMP Negeri 1 Padang and the research sample consisted of 201 students who were taken using random sampling technique. The instruments that used were arranged based on the constructs of the three variables, namely school well-being, emotional intelligence and student engagement in learning that had met the validity and reliability requirements. The research data were analyzed using simple regression and multiple regression. The findings of the study show that: (1) in average, student engagement in learning is in the high category, (2) school well-being and emotional intelligence are also in the high category, (3) the contribution of school well-being to student engagement in learning by 48.2%, (4) the contribution of emotional intelligence to student engagement in learning by 57%, and (5) the contribution of school well-being and emotional intelligence together to student engagement in learning by 62.1%. The implications of the research results can be used as a basis in the preparation of guidance and counseling service programs.